Genomic Variability of Haemophilus influenzae Isolated from Mexican Children Determined by Using Enterobacterial Repetitive Intergenic Consensus Sequences and PCR - Gomez-De-Leon, Patricia (American Society for Microbiology, 2000)
Genomic fingerprints from 92 capsulated and noncapsulated strains of Haemophilus influenzae from Mexican children with different diseases and healthy carriers were generated by PCR using the enterobacterial repetitive intergenic consensus (ERIC) sequences. A cluster analysis by the unweighted pair-group method with arithmetic averages based on the overall similarity as estimated from the characteristics of the genomic fingerprints, was conducted to group the strains. A total of 69 fingerprint patterns were detected in the H. influenzae strains. Isolates from patients with different diseases were represented by a variety of patterns, which clustered into two major groups. Of the 37 strains isolated from cases of meningitis, 24 shared patterns and were clustered into five groups within a similarity level of 1.0. One fragment of 1.25 kb was common to all meningitis strains. H. influenzae strains from healthy carriers presented fingerprint patterns different from those found in strains from sick children. Isolates from healthy individuals were more variable and were distributed differently from those from patients. The results show that ERIC-PCR provides a powerful tool for the determination of the distinctive pathogenicity potentials of H. influenzae strains and encourage its use for molecular epidemiology investigations.